THE FACTOR ASSOCIATED WITH RECOVERY OF MALAYSIA AIRLINES - shukri, Sakinah mohd; Yajid, Mohd Shukri Ab; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
This study explore the factors effecting the recovery of airlines in Malaysia. Previously a government agency, later known as Malaysian Airline System (MAS) embarked on a system of corporate governance that would ensure the fulfillment of its role not only as a national carrier but also as a corporate citizen centered on being responsible to its shareholders. In this new age of technology after the economic downturn and the 9/11 incident, Malaysia Airlines and all other airline companies throughout the world had suffered a long term running at loss due to drastic changes of market pattern. Malaysia Airlines had taken various strategies in diversifying its operations into human resource development, training, catering, property consultancy and technical ground support for aircrafts to cater the decreasing demand of services. Sharing its limelight with the ultra-modern Kuala Lumpur International Airport (KLIA), Malaysia Airlines also provides world-class cargo management facilities to meet the needs of all potentials. With more than 50 years of experience, Malaysia Airlines is now still seeking the ways to cater to the ever growing needs of fast moving travelers and bringing them the best service that air travel has to offer such as sophisticated in-flight entertainment to the simple things in life. Malaysia Airlines tries to offer the world-class services that somehow redefines the standards in passengers’ comfort that fulfill their needs and wants against each and every rival internationally as well as domestically. Now, Malaysia Airlines is Malaysia’s biggest carrier with a fleet of about 110 aircrafts that fly passengers and cargo to more than 100 cities across six continents. Despite the worldwide issues, Malaysia Airlines continues to firmly establish the brand name as Asia’s leading carrier and the company is now spreading its wings to more than 200 destinations across the globe (Al-Jader & Sentosa, 2015; De Silva et al., 2018a; De Silva et al., 2018b; Nikhashemi et al., 2013).